Cellular and molecular characterization of γδ T cells in peripheral blood from patients with metastases from cutaneous and uveal melanoma - Alonso-Agudo, Tamara; Johansson, Junko; Ståhlberg, Anders; Olofsson Bagge, Roger (Frontiers in Immunology, 2025)
T cells can be divided into two major subtypes based on which chains that make up the T cell receptor (TCR): the conventional αβ T cells and the less common γδ T cells. γδ T cells are attractive targets of cancer immunotherapy due to e.g. their independence from MHC-restricted activation. Despite the successful implementation of immune checkpoint inhibitors for the treatment of metastatic melanoma, not all patients respond favorably to the treatment. In this study we characterized γδ T cells in peripheral blood from patients with cutaneous and uveal melanoma, and from age-matched healthy controls, with ultrasensitive DNA sequencing (SiMSen-Seq) of the δ-chain and flow cytometry to facilitate the introduction of γδ T cell-based treatment strategies. As a general trend, the Vδ1+ subpopulation was found to be more abundant in patients labeled as responders versus non-responders. Regarding clonal diversity, although a high oligoclonality was found in each individual and within each group, clonal diversity was lower in patients labeled as responders to treatment. Cutaneous melanoma patients had a larger total number of clonotypes compared to the healthy controls, and did also express higher levels of the receptor NKG2D on the surface of Vδ2+ cells. Overall, we could see small differences between cutaneous and uveal melanoma patients and healthy controls in regard to distribution of γδ subpopulations, with high clonal diversities and a mostly private repertoire of the δ receptor among all groups.